Investigating the effects of diurnal and nocturnal pollinators on male and female reproductive success and on floral trait selection in Silene dioica - Barbot, Estelle; Dufaÿ, Mathilde; Godé, Cécile; De Cauwer, Isabelle (Peer Community Journal, 2025)

(untitled)
Plant species with mixed pollination systems are under pollinator-mediated selection by both diurnal and nocturnal pollinator species. This could impact the strength and potentially direction of selection on floral traits, as different pollinators are not necessarily attracted by the same traits. In this study, we investigated how selection gradients on floral traits in Silene dioica were affected by (i) the pollinator community the plants were exposed to (diurnal versus nocturnal pollination) and (ii) the level of emission of a volatile organic compound typically linked to pollinator attraction (natural versus enhanced phenylacetylaldehyd (PAA) emission) in a fully crossed design. Female plants in all treatments achieved full seed set, suggesting no differences in pollination efficiency between diurnal and nocturnal pollinator communities in S. dioica. Nocturnal pollination resulted in stronger selection on corolla width and flower number in males, but not in females. We further found that increased PAA emission modified selection on attractive traits both in plants exposed to diurnal and nocturnal pollinators, with a stronger effect in males. This stronger response of selection patterns to pollinator community and scent emission could suggest that males are more dependent on pollinator attraction than females in their reproductive success.